Nation and sporting places: exploring the national stadia of a (dis)United Kingdom - Bairner, Alan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The focus of this paper is sports stadia in Britain and Ireland and, by implication, the politics of identity in a multi-national United Kingdom, arguably more divided than at any time since the Act of Union in 1707 because of the decision to leave the European Union. The paper discusses sports stadia in England, Scotland, Wales and Northern Ireland and, by necessary extension, the Republic of Ireland.
Keywords: sport; stadia; nationalism; United Kingdom the; Republic of Ireland